2011
DOI: 10.1152/ajpcell.00479.2010
|View full text |Cite
|
Sign up to set email alerts
|

Zip14 is a complex broad-scope metal-ion transporter whose functional properties support roles in the cellular uptake of zinc and nontransferrin-bound iron

Abstract: Here, we directly tested the hypothesis that Zip14 transports free zinc, iron, and other metal ions by using the Xenopus laevis oocyte heterologous expression system, and use of this approach also allowed us to characterize the functional properties of Zip14. Expression of mouse Zip14 in RNAinjected oocytes stimulated the uptake of 55 Fe in the presence of L-ascorbate but not nitrilotriacetic acid, indicating that Zip14 is an iron transporter specific for ferrous ion (Fe 2ϩ ) over ferric ion (Fe 3ϩ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
171
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 190 publications
(182 citation statements)
references
References 47 publications
9
171
1
1
Order By: Relevance
“…Although K m or normalized V max values between differing expression systems may vary, it is likely that trends, such as mutations that result in higher/lower affinities or changes in normalized V max , will be consistent between overexpression systems. Furthermore, considering that both micromolar and nanomolar K m values have been observed upon heterologous expression in mammalian cells as well as X. laevis oocytes, this suggests that either both affinities are present in vivo or that overexpression in both cell types gives equivalent artifacts (3,4,46). Therefore, analysis of hZIP4 transport experiments performed in X. laevis oocytes is a viable and valuable method to examine transport properties for this class of proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although K m or normalized V max values between differing expression systems may vary, it is likely that trends, such as mutations that result in higher/lower affinities or changes in normalized V max , will be consistent between overexpression systems. Furthermore, considering that both micromolar and nanomolar K m values have been observed upon heterologous expression in mammalian cells as well as X. laevis oocytes, this suggests that either both affinities are present in vivo or that overexpression in both cell types gives equivalent artifacts (3,4,46). Therefore, analysis of hZIP4 transport experiments performed in X. laevis oocytes is a viable and valuable method to examine transport properties for this class of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Although mutations to these proteins result in cellular zinc and/or iron deficiency, analysis of in situ experiments have demonstrated that ZIP transporters can also transport Ni 2ϩ , Cu 2ϩ , and/or Cd 2ϩ (3,4). ZIP member proteins have eight transmembrane domains and can be further classified into subfamilies (ZIPI, ZIPII, gufA, and LIV-1) based on sequence alignments (5).…”
mentioning
confidence: 99%
“…NTBI is taken up by the liver via ZRT/IRT-like protein-14 (ZIP14/SLC39A14), a transmembrane metal-ion transporter located on the sinusoidal membrane of hepatocytes (72). ZIP14 was originally identified as a zinc transporter, but subsequent studies showed that it could also transport iron (73,74) and that its protein levels in liver increase in response to iron loading (72). Slc39a14-null mice display markedly impaired uptake of intravenously administered 59 Fe-NTBI and fail to load iron in hepatocytes when the mice are fed an iron-loaded diet or crossed with mouse models of hereditary hemochromatosis (75).…”
Section: Hepatocyte Iron Metabolismmentioning
confidence: 99%
“…2D and 5D) supports the notion that GRP94 is a critical factor that supports recovery of ER homeostasis. Although ZIP14 can contribute to uptake of manganese and non-transferrinbound iron under certain circumstances (49,50), the hepatic concentration of these metals after TM administration was comparable between WT and Zip14 KO mice (Fig. S1 E and F).…”
Section: Discussionmentioning
confidence: 97%